ANALISIS WACANA DIMENSI TEKS MODEL VAN DIJK PADA TEKS BERITA KRITIK PEMERINTAHAN JOKOWI - La Ode Adili Adili (Balai Bahasa Sulawesi Tengah, 2015)
This study aimed to describe the text-dimensional model of Van Dijk in the text of news “Criticism of Jokowi’s Government”. The method use is a qualitative research. Teh result shows that the text-dimensional model of Van Dijk divided into three parts, they are: macro-structure, super-structure, and micro-structure. Those can be found in the text of news “Criticism of Jokowi’s Government”. In the dimensional of macrostructure, the writer focused on the topic or theme in each of the text. As well as the the dimention of super-structure, the writer presented the whole part of the sentences and the text sequences. At the dimension of micro-structure, there are elements the writer used, such as: background, details, goals, pre-assumption, nominalization, form of sentences, coherence, pronouns, lexicon, graphics, and metaphor (figure of speech).